Process matters: South Africa's experience exiting its BITs - Mohammad Mossallam (University of Oxford, Global Economic Governance Programme (GEG), 2015)
This paper examines South Africa's policy decision to review and exit its Bilateral Investment Treaties (BITs). Drawing on interviews with government officials and business representatives, public documents and secondary literature, it scrutinises the process that South Africa went through in reviewing its investment policies, its decision to terminate its BITs and to enact new domestic legislation for investor protection. The paper illustrates that the decision of the South African government to change its policies on investment was triggered by a concern that BITs and the international system of investor-state arbitration inhibits the ability of governments to enact legislation and regulatory measures aimed at promoting public policy objectives. While the review undertaken by South Africa may have its shortcomings, which the paper highlights, it has been lauded as a thorough and critical approach through which it has sought to build its internal capacity on the topic of investment. Documenting this fascinating process provides valuable insights into the drivers of investment policy reform and useful lessons for other developing counties who may wish to embark on a similar exercise.
Keywords: 330; Auslandsinvestition; Internationales Investitionsrecht; Südafrika